Augmentation of germination in Sapindus mukorossi due to acid scarification in Jhanjhatpur nursery - Thapa, H.B.; Gautam, S.K. (Banko Janakari, 2007)
The study on ‘effects of pre-sowing treatments on germination of Sapindus mukorossi Gaertn,’ was carried out in Jhanjhatpur nursery, Kailali district in April 2004. About 15- months old healthy seeds were treated in one of thirty ways before sowing and sown from 1 to 7 April 2004 in drills in a nursery bed at a spacing of 5 cm x 10 cm. The analysis revealed that thirty pre-treatments significantly differed in germination in 1-month (4-weeks) and 2-months (9-weeks) but these pre-treatments did not vary in 3-months (13-weeks). In 4-weeks, the pre-treatment, 90-minutes in concentrated hydrochloric acid significantly differed with twenty-five pre-treatments except the four pre-treatments of 15, 45, 60 and 75 minutes in concentrated acid. The highest germination (90%) was found in the pretreatment, 90-minutes in acid, which was followed by the germination (63%) in the pretreatment, 75-minutes in concentrated acid in 3-weeks. The highest non-germinated good seeds were in pre-treatment, 30% in 96 hours in cold water, followed by the pre-treatment, 27% in 5-minutes in boiled water and 72-hours in cold water. The highest non-germinated rotten seeds were in the pre-treatments, 3-minutes in boiled water and 72-hours in cold water and 10 minutes in acid, followed by the five pre-treatments, 3-minutes in boiled water and 120 hours in cold water, 5-minutes in boiled water then 24 and 72 hours in cold water, 5-minutes and 60-minutes in concentrated acid. The two pre-treatments, 75 and 90 minutes in concentrated acid can be used to get quicker and higher germination. The four pre-treatments, 3 minutes in boiled water and 48 hours in cold water, 5-minutes in boiled water and 120 hours in cold water, 144 hours in cold water and 120 hours in cow dung slurry are suggested as an alternative to acid treatments, if acid is not readily available in the market and there is a problem of handling the acid. Key words: Sapindus mukorossi, germination, acid, pre-treatment Banko Janakari Vol.16(1) 2006 pp14-20